PENGARUH MOTIVASI, EFIKASI DIRI DAN DISIPLIN KERJA TERHADAP KINERJA GURU PADA SMP NEGERI 7 DENPASAR - Ni Made Satya Utami; Ni Putu Ayu Sintya Saraswati; Ni Kadek Ayu Martini (VALUES, 2024)
Maximizing human resources is the main focus in institutions generally in improving teacher performance. Teacher performance is influenced by many factors such as motivation, self-efficacy and work discipline. This research aims to determine the influence of work motivation, self-efficacy and work discipline on teacher performance. The location of this research is at SMP Negeri 7 Denpasar. The population used teachers at SMP Negeri 7 Denpasar and a sample of 50 teachers. Data analysis techniques use Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Multiple Correlation Test, Determination Coefficient, F Test and t Test. From the research results, it was found that work motivation had a positive and significant effect on teacher performance, self-efficacy had a positive and significant effect on teacher performance, and work discipline had a positive and significant effect on teacher performance. Suggestions that can be given by researchers are that teachers at SMP Negeri 7 Denpasar should always increase their motivation to achieve the vision and mission of the SMP Negeri 7 Denpasar institution, provide training to teachers to increase teachers' self-confidence in teaching students, give strict sanctions to teachers who make mistakes, provide motivation to teachers so that later teachers can achieve the targets that have been set.